Early pubertal development and insulin sensitivity among school-aged girls: mediation via adiposity - Hillman, Jennifer B. (2012)
STUDY OBJECTIVE: To examine whether the known association between early pubertal breast maturation and insulin sensitivity (SI) is mediated by adiposity. DESIGN: Cross-sectional analyses, Setting: Observational study examining the roles of environment, diet, and obesity on puberty PARTICIPANTS: 379 girls with a mean age, 7.03 years; 62% were white and 29% black MAIN OUTCOME MEASURE(S): Pubertal development was assessed via physical examination and adiposity by body mass index Z score (BMI Z) and waist-to-height ratio. Fasting blood samples were obtained for insulin and glucose concentrations. SI was calculated with the quantitative insulin sensitivity check index (QUICKI). Analysis of variance and Sobel’s test was used to assess mediation. RESULTS: Fifty-five girls were pubertal (Tanner 2 breast). Breast maturation was inversely associated with SI (p=.005) and positively associated with BMI Z (p<.001) and waist-to-height ratio (p<.001). The effect of breast maturation on SI was no longer significant (p=.41) after adjusting for the effect of BMI Z, which remained significant (p<.001). Similar results were obtained when waist-to-height ratio replaced BMI Z in the models. Mediation analyses demonstrated that 75% of the association between breast maturation and SI is mediated by adiposity. CONCLUSIONS: In girls, decreased SI during early puberty is largely mediated by total and visceral adiposity.